PENINGKATAN KEMAMPUAN BAHASA JAWA ANAK MELALUI BERMAIN DRAMA MUSIKAL PADA ANAK KELOMPOK A5 DI BUSTANUL ATHFAL RESTU 1 MALANG - Yuli Fitriani; Khoirul Asfiyak; Yorita Febry Lismanda (UNISMA, 2019)
This study aims to find out whether there is an increase in Javanese language skills on A5 children in BA Restu 1 in the sub-district of Malang. This action research takes the form of research collaboration, where the class action researchers collaborate with teachers who are members of one team to conduct research with the aim to fix deficiencies. The study was conducted in 2 cycles. This research was conducted on A5 children in the blessing of 2018/2019 academic year. In this study, researchers used three data collection techniques in the form of observation, interviews, and documentation. data collection instrument are observation sheets, RPPH, and photosof activities. Based on the results of the average value, the A5 child has increased. in the first cycle the total value was 1444.3 with an average score of 60.1. Then the evaluation in cycle II gets a total value of 1931.4 with an average value of 80.5 children. So that learning in cycle II had been completed and could improve children's A5 language skills in BA RESTU 1 Klojen sub-district Malang City.